Use of PRF for repair of alveole after exodontia of third molars (Research, Society and Development, 2021)
Fibrin Rica em Plaquetas (PRF) is an autologous process, which consists in the removal of a blood sample taken from the patient, where it is placed in a test tube, later centrifuged, and deposited in the alveole after extraction of the third molar. This therapy is still in advances, but it has been used more and more in the extractions of third molars, where it helps in bone and tissue regeneration. The objective of this work is to highlight the influence of PRF on tissue and bone regeneration, including its use and its benefits in alveolos after exodontia. The methodology was to perform a narrative review of the literature and researched works in scientific databases, such as: Scielo, PubMed and LILACS in the period from 1996 a 2020. Thus, Fibrina Rica em Plaquetas acts as an adjunct in bone and tissue healing and regeneration, and because it is an autologous process the risks of rejection are minimal. It is concluded that the PRF is a process that is still in progress, however, it is a great alternative for the regeneration of alveolos after extractions of third molars, because it has unique biological properties.